2022
DOI: 10.3389/fmicb.2022.1055996
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic next-generation sequencing for identification of central nervous system pathogens in HIV-infected patients

Abstract: Although considerable interest in metagenomic next-generation sequencing (mNGS) has been attracted in recent years, limited data are available regarding the performance of mNGS in HIV-associated central nervous system (CNS) infection. Here, we conducted a retrospectively analyzing of the cerebrospinal fluid (CSF) mNGS reports and other clinical data from 80 HIV-infected patients admitted to the Second Hospital of Nanjing, China from March, 2018 to March, 2022. In our study, CSF mNGS reported negative result, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…The patient had poor response to antiviral treatment and clinical symptom and pleocytosis were improved quickly after steroid pulse therapy, which also support the notion of EBV‐induced CNS autoimmune response. Variable numbers of EBV from one to thousands of sequence reads were reported by CSF mNGS in EBV encephalitis 8 . Low sequence reads of EBV in CSF cannot eliminate the possibility of its active infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient had poor response to antiviral treatment and clinical symptom and pleocytosis were improved quickly after steroid pulse therapy, which also support the notion of EBV‐induced CNS autoimmune response. Variable numbers of EBV from one to thousands of sequence reads were reported by CSF mNGS in EBV encephalitis 8 . Low sequence reads of EBV in CSF cannot eliminate the possibility of its active infection.…”
Section: Discussionmentioning
confidence: 99%
“…Variable numbers of EBV from one to thousands of sequence reads were reported by CSF mNGS in EBV encephalitis. 8 Low sequence reads of EBV in CSF cannot eliminate the possibility of its active infection.…”
Section: Discussionmentioning
confidence: 99%
“…In people living with HIV, accumulating evidence has shown that mNGS may help to identify the aetiological agents when conventional methods have failed to diagnose the CNS infection [12][13][14][15]. However, most studies have only focused on clinical cases caused by novel or rare pathogens [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…There are several techniques to identify C. psittaci , including serological techniques, isolation, direct immunoenzymatic tests and polymerase chain reaction (PCR) ( Mahony et al., 1993 ; Longbottom and Coulter, 2003 ; Jeong et al., 2017 ). Metagenomic next-generation sequencing (mNGS) is a new technique that has been widely used in the diagnosis of pathogens in patient infected by human immunodeficiency virus ( Zhu et al., 2022 ), especially when clinicians cannot determine the pathogen causing the disease ( Gu et al., 2019 ). In recent years, with improvements in detection methods and understanding of the disease, reported cases of psittacosis have been increasing.…”
Section: Introductionmentioning
confidence: 99%